Ethics in Psychiatric Research: A Review of 25 Years of NIH-funded Empirical Research Projects - DuBois, James (2011)
BACKGROUND: This paper reviews the past 25 years of empirical research funded by the National Institutes of Health (NIH) on matters of ethics in psychiatric research. METHODS: Using the NIH RePORTER and Medline databases, we identified 43 grants and 77 publications that involved the empirical study of a matter of ethics in research involving mental health service users. RESULTS: These articles provide original and useful information on important topics, most especially the capacity to consent and the voluntariness of consent. For example, participants who share a diagnosis vary widely in levels of cognitive impairment that correlate with decisional capacity, and capacity to consent can be enhanced easily using iterative consent processes. Few articles address matters of justice or benefits in research, particularly from the perspectives of participants. No articles address matters of privacy, confidentiality, or researcher professionalism. CONCLUSIONS: Despite the usefulness of data from the studies conducted to date, current research on research ethics in psychiatry does not adequately address the concerns of service users as expressed in recent publications.